USING SPREADSHEET SOFTWARE TO PLOT DISTRIBUTION CURVES IN FORENSIC ANALYSIS OF POWDERS (A CASE STUDY OF POLYMER POWDER) - A. Shirokov (Теория и практика судебной экспертизы, 2015)
Polymer powder research for establishment of the sizes of its particles is considered. The step-by-step way of processing of empirical data for plotting of distribution of particles by the sizes is described and is shown that use thus of tabular processors significantly allows to simplify performance of necessary calculations.